2007
DOI: 10.1093/toxsci/kfm070
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Gene Expression and Testosterone Synthesis in the Testes of Male Rats Exposed to Perfluorododecanoic Acid

Abstract: Perfluorododecanoic acid (PFDoA, C12), a synthetic perfluorinated chemical containing 12 carbons, has broad industrial applications and has been detected in sera from humans and other animals; however, few reports have addressed the effects of PFDoA exposure on male reproduction. In the present study, the effects of PFDoA exposure on testes ultrastructure, testosterone levels, and steroidogenic gene expression were investigated. Male rats were orally dosed for 14 days with 1, 5, or 10 mg PFDoA/kg/day or with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 40 publications
8
88
2
5
Order By: Relevance
“…The cytochrome P-450 aromatase enzyme, the ratelimiting enzyme in estradiol biosynthesis, it catalyzes the estradiol sythesis from testosterone. The present study demonstrated that aromatase mRNA levels decreased in TiO2 administered rats and NAC normalized aromatase expression in a way to control estradiol biosynthesis (Shi et al, 2007). It has been shown that NAC decrease diazinon induced oxidative stress in rat testes (Oksay et al, 2013) and improved semen quality and canine fertility (Michael et al 2010).…”
Section: Ajptsupporting
confidence: 54%
“…The cytochrome P-450 aromatase enzyme, the ratelimiting enzyme in estradiol biosynthesis, it catalyzes the estradiol sythesis from testosterone. The present study demonstrated that aromatase mRNA levels decreased in TiO2 administered rats and NAC normalized aromatase expression in a way to control estradiol biosynthesis (Shi et al, 2007). It has been shown that NAC decrease diazinon induced oxidative stress in rat testes (Oksay et al, 2013) and improved semen quality and canine fertility (Michael et al 2010).…”
Section: Ajptsupporting
confidence: 54%
“…Previous studies reported that certain PFCs, such as PFOA, PFDA, and PFDoA decreased serum testosterone level in rats under toxicological dosages (Bookstaff et al, 1990;Martin et al, 2007;Shi et al, 2007Shi et al, , 2009). The serum PFCs concentrations (5 μg/mL to 260 μg/mL) measured in those dosed animals were in the same range as the concentrations of FTOHs applied to H295R cells in this study Martin et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the down-regulation of mRNA expression and protein abundance could lead to the decreased steroid hormone production. It has been previously demonstrated that exposure to PFDoA significantly decreases StAR and P450scc (CYP11A) mRNA expression and protein abundance resulting in decreased serum testosterone concentrations in male rat testes (Shi et al, 2007(Shi et al, , 2009). The authors speculated that decreased testosterone level, at least in part, was due to the reduced expression of StAR and CYP11A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to receptor-mediation capacity, PFCs have also been shown to alter hormone production by affecting steroidogenic tissue in reproductive organs [16,17,28]. To explore the mechanism of steroidogenesis disruption by PFOS, concentrations of two steroid hormones (T and E2) in the culture medium and relative responses of 10 genes involved in the steroidogenic pathway were measured in H295R cells.…”
Section: Discussionmentioning
confidence: 99%